Strength and endurance preparation and the effectiveness of sports training in gymnasts aged 11-13 - Kochanowicz, A.; Kochanowicz, K. (Journal of Kinesiology and Exercise Sciences, 2010)
Aim of the work. Directing a sports training in artistic gymnastics is based on justified values of control allowing the diagnosis and prognosis of the development of special fitness and athletes` sports results. The aim of the study was to determine the interdependence between strength-endurance skills and sports preparation in athletes of selected gymnastic events at the stage of directed training. Material and methods. 15 boys aged 11-13 practising artistic gymnastics at the stage of directed training in the MKS AZS AWFiS Gdañsk and the Sports Mastery School in Gdansk were subject to the study. The study was carried out in laboratory, training and competitive conditions in 2004-2007. Results. An analysis of results allowed indicating the most informative strength-endurance indices having a significant correlation with the technical preparation in the following events: pommel horse, rings, parallel bars and H-bar. Quantitative criteria of the following indices have been worked out: strength-endurance, special fitness and technical preparation in half-yearly macrocycles of the training process. Individual profiles of special fitness with an indication at their changeable character in the three-year study period have been presented. Conclusions. 1.The most significant in the control at the directed training stage in gymnasts are indices of relative isometric strength of upper extremities flexors and the isokinetic strength endurance of upper extremities extensors. 2. The study results allowed to work out the criteria of assessment of strength-endurance skills and the level of sports preparation which enable referring various control indices to the syllabus requirements posed in the specific half-yearly macrocycle in a unified point scale. 3. Creating individual profiles of special fitness enables optimisation of the training process in particular training macrocycles.